The Effect of Digital Leadership on Performance through Task-Technology Fit and AI Literacy in Creative Industries - Dwi Novitasari; Mohamad Yusak Anshori; Fadia Jasmine Has Shiela (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Digital transformation reshapes organizations, requiring leaders to leverage technology for enhanced performance. This study explores how digital leadership influences performance orientation through task-technology fit and artificial intelligence literacy in Indonesia’s creative and technology sectors. The objective is to examine the mediating roles of task-technology fit, the alignment of technology with tasks, and artificial intelligence literacy, the ability to use and understand artificial intelligence tools, in driving performance. A quantitative approach was employed, using a survey of 300 professionals in Yogyakarta, analyzed with Structural Equation Modeling (SEM). The findings show that digital leadership significantly enhances task–technology fit and AI literacy, which in turn strengthens performance orientation. Both mediators partially transmit leadership effects, revealing structural and cognitive pathways in digital workplaces. Organizations should invest in digital leadership development, AI literacy initiatives, and systematic alignment between workflows and technologies to build agile, performance-focused cultures. These efforts can enhance innovation, support evidence-based decision making, reduce technostress, and prepare creative and technology workers to collaborate effectively with AI.